1000 Wh L−1 lithium-ion batteries enabled by crosslink-shrunk tough carbon encapsulated silicon microparticle anodes. Issue 9 (23rd January 2021) - Chen, Fanqi; Han, Junwei; Kong, Debin; Yuan, Yifei; Xiao, Jing; Wu, Shichao; Tang, Dai-Ming; Deng, Yaqian; Lv, Wei; Lu, Jun; Kang, Feiyu; Yang, Quan-Hong
Abstract: Microparticulate silicon (Si), normally shelled with carbons, features higher tap density and less interfacial side reactions compared to its nanosized counterpart, showing great potential to be applied as high-energy lithium-ion battery anodes. However, localized high stress generated during fabrication and particularly, under operating, could induce cracking of carbon shells and release pulverized nanoparticles, significantly deteriorating its electrochemical performance. Here we design a strong yet ductile carbon cage from an easily processing capillary shrinkage of graphene hydrogel followed by precise tailoring of inner voids. Such a structure, analog to the stable structure of plant cells, presents 'imperfection-tolerance' to volume variation of irregular Si microparticles, maintaining the electrode integrity over 1000 cycles with Coulombic efficiency over 99.5%. This design enables the use of a dense and thick (3 mAh cm –2 ) microparticulate Si anode with an ultra-high volumetric energy density of 1048 Wh L –1 achieved at pouch full-cell level coupled with a LiNi0.8 Co0.1 Mn0.1 O2 cathode. Abstract : An imperfection-tolerant carbon capsule cellular architecture well accommodates irregular microparticulate silicon anodes which represents a critical step forward in building compact lithium-ion batteries approaching ultrahigh volumetric energy density.